Penerapan Prinsip Partisipasi Publik Dalam Pembentukan Undang-Undang Nomor 1 Tahun 2023 Tentang Kitab Undang-Undang Hukum Pidana - Herlanty, Febrima; Yuliandri, Yuliandri; Fahmi, Khairul (Faculty of Law, Andalas University, 2025)
In the formation of laws, one of the important things is public participation. Public participation is regulated by Article 96 of Law No. 13 of 2022 on the Second Amendment of Law No. 12 of 2011 on the making of laws. The issues in this study are: 1) How was the standard of meaningful participation implemented by the government in the enactment of Law No. 1 of 2023 on the Criminal Code? 2) Was the principle of meaningful participation met in the enactment of Law No. 1 Year 2023 on the Penal Code? The type of research is Normative research. The conclusions of this research are: 1. The norm of fulfillment of participation in the preparation of the Penal Code from 1961 to the present has been conducted on the basis of INPRES Number 15 of 1970, KEPRES 188 of 1998 and Law Number 13 of 2022 concerning the second amendment of Law Number 12 of 2011. 2. The application of the principle of meaningful participation in the drafting of the Criminal Code has been carried out through public hearings, public dialogue, socialization and discussion forums, and public contributions have been made, including the deletion of 6 articles, reformulation or amendment of 57 articles, addition of 2 new articles and addition of content to 1 article, and repositioning of 4 articles.